Relationship among Tobacco Habits, Human Papilloma Virus (HPV) Infection, p53 Polymorphism/Mutation, and the Risk of Oral Squamous Cell Carcinoma - Neha Gupta; Gargi Yumnam; Chetan Sharma; Avani Patel; Ripudaman Sharma; Sachin Dev; Mahesh Ghadage (Journal of Pharmacy and Bioallied Sciences)
Background: Oral squamous cell carcinoma (OSCC) is a multifactorial malignancy influenced by various genetic and environmental factors. Tobacco habits, human papilloma virus (HPV) infection, and p53 polymorphisms or mutations have been implicated in its etiology. Understanding their interplay can provide insights into OSCC risk assessment. Materials and Methods: A case–control study was conducted among 300 OSCC patients and 300 age- and sex-matched controls. Data on tobacco use (smoking and smokeless), HPV infection status (detected via PCR), and p53 polymorphism/mutation (analyzed by sequencing) were collected. Statistical analysis included logistic regression to assess the associations and interactions among these variables. Results: Among OSCC cases, 75% were tobacco users compared to 35% in controls. HPV prevalence was significantly higher in OSCC cases (30%) than controls (5%). P53 mutations were identified in 40% of OSCC cases compared to 10% in controls. Logistic regression revealed synergistic effects between tobacco use and HPV infection (OR 5.2, 95% CI 3.0–9.0) and additive effects with p53 mutations (OR 3.5, 95% CI 2.0–6.0). Conclusion: Tobacco habits, HPV infection, and p53 polymorphisms/mutations independently and synergistically contribute to the risk of OSCC. Strategies focusing on tobacco cessation, HPV vaccination, and genetic screening may help mitigate OSCC risk in susceptible populations.